Incremental peritoneal dialysis: less is more—for the patient and the planet - Nardelli, Luca; Scalamogna, Antonio; Alfieri, Carlo; Alberici, Federico; Castellano, Giuseppe (Frontiers in Medicine, 2025)
Climate change poses growing threat to global health, and paradoxically, the health-care sector—including nephrology—is a significant contributor to greenhouse gas (GHG) emissions. Dialysis, in particular, is resource-intensive. Yet, dialysis remains life-saving for over 4 million people globally, a number projected to rise sharply. While peritoneal dialysis (PD) offers a home-based alternative to hemodialysis with potentially lower environmental costs, it still generates considerable carbon emissions and waste—especially from the production, packaging, and transport of dialysate solutions. A typical continuous ambulatory PD patient generates over 600 kg of waste per year, much of it non-biodegradable polyvinyl chloride. PD’s carbon footprint ranges from 1.2 to 4.5 tons of CO₂-equivalent annually, primarily from packaging and transport. Incremental peritoneal dialysis (iPD)—an approach that starts therapy at a reduced dose based on residual kidney function (RKF)—offers a more sustainable model. Incremental PD reduces water usage, plastic waste, and carbon emissions by as much as 30–45% compared to full-dose PD. Clinically, iPD is associated with better quality of life, fewer infections, less glucose exposure, and potential preservation of RKF. Economically, it offers substantial cost savings, with estimates up to €8,700 saved annually per patient. Despite its benefits, barriers to iPD adoption include provider unfamiliarity, patient reluctance to intensify treatment, reimbursement limitations, and the need for close RKF monitoring and clinical assessment. Addressing these challenges through policy reform, education, and digital tools could enable broader implementation of iPD, aligning kidney care with environmental stewardship.